Implementasi Peraturan Daerah No.14 tahun 2006 tentang Retribusi Izin Usaha Perdagangan Minuman Beralkohol di Kota Pekanbaru - ASTRID PURBA; Febri YULIANI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of Regional Regulation No. 14 of 2006 about Retribution Business Permission of Alcohol Trade in PekanbaruPermission become a problem on process of circulate and selling alcohol in Pekanbaru . It’s because there is connection about supply and demand between sales and buyer of alcohol. In Pekanbaru, process of circulate sponsored by night club , discotic and karaoke which have sprung up in this city. Actually , there is already regional regulation that useful for controlling process of circulate alcohol.Theory implementation of Van Meter and Van Horn have six variables which arranged connection between policy and performance such as : policy purpose , resources , communication between implementors , characteristic of implementor , condition of social,economy and politics and also disposition of implementors. This research used qualitative method and also used snow ball sampling which used key informan . Satpol PP and Disperindag Pekanbaru City are the key informan for this research.Based on research , Implementation of Regional Regulation no. 14 of 2006 about Retribution Business Permission of Alcohol Trade in Pekanbaru has been done by Satpol PP and Disperindag but implementation hasn’t been done like a real content. There’s no sanction in every mistakes which has been done by sales of alcohol. Communication between Disperindag and Satpol PP really limited and also no repair for regional regulation.Keywords : Implementation, Regional Regulation , Permission , Alcohol